PEMERIKSAAN GOLONGAN DARAH PELAJAR TAMAN KANAK-KANAK ISLAM TERPADU (TKIT) AL QALAM MAKASSAR - Sulfiani Sulfiani; Basmiati Basmiati; Nuralam Sobak; Riski Handayani (Batara Wisnu : Indonesian Journal of Community Services, 2021)
Knowing blood type is an important part for every human being. Many of us do not know what type of blood type we have. This case becomes very crucial when the individual experiences a disaster. The action of handling the patient becomes late, because this individual does not yet know the type of blood group he has. Knowing your blood type helps the body stay healthy, plan for the future and prevent complications. The implementation method in this community service activity begins with the planning stage by conducting site surveys and interviews with the school, the preparation stage by preparing equipment in the form of tools, materials and other equipment and the implementation stage by opening and checking blood groups and distributing blood group identity cards. This activity was well received by the school and students. The number of students who carried out the examination was 26 people with a percentage of 42.31% male students and 57.69% female students. The results of the blood group examination obtained by the students of TKIT Al-Qalam Makassar are having blood group A (42.31%), blood type B (26.92%), blood type AB (7.69%) and blood type O (42, 31%).